INSTITUTIONAL DETERMINANTS OF OIL MARKET FORMATION IN THE CONDITIONS OF MODERN WORLD ENERGY RESOURCES POLICY - Donets, D. М. (The actual problems of regional economy development, 2024)
The article discusses the institutional determinants influencing the formation of the oil market within the framework of modern global energy policies at both international and state levels. Various general scientific and specialized research methods, including inductive and deductive approaches, were employed in analyzing the activities of international organizations affecting Ukraine's oil market. Comparative analysis was conducted to examine the roles of international and domestic institutions in shaping the oil market. Graphical methods were utilized to visually represent the international and state organizations impacting the oil market. The abstract-logical method facilitated generalizations and consolidation of research findings. The authors argue that oil market regulation considers both state and international institutions. They explore the activities of international organizations such as the Organization of Petroleum Exporting Countries, the International Energy Agency, the International Atomic Energy Agency, the World Trade Organization, and the International Monetary Fund, which significantly influence the global oil market and, consequently, Ukraine's domestic market. Ukraine's oil market is governed by several institutions and authorities responsible for overseeing petroleum production, supply, trade, and consumption. Key influencers on Ukraine's oil market include the Verkhovna Rada of Ukraine, the Ministry of Energy and Environmental Protection of Ukraine, the State Service of Ukraine for Supervision of Labor Protection, the State Inspection for Control of Fuel Quality and Compliance with Standards, the Antimonopoly Committee of Ukraine, the State Customs Service of Ukraine, and the National Commission for State Regulation in the Energy and Utilities Sectors. The determinants affecting the demand, supply, and prices of petroleum products are examined, with a focus on global oil demand, geopolitical factors, production costs and technologies, oil reserves and production, development of alternative energy sources, and exchange rates.